2012
DOI: 10.1002/cpe.2845
|View full text |Cite
|
Sign up to set email alerts
|

General‐purpose computation on GPUs for high performance cloud computing

Abstract: SUMMARY Cloud computing is offering new approaches for High Performance Computing (HPC) as it provides dynamically scalable resources as a service over the Internet. In addition, General‐Purpose computation on Graphical Processing Units (GPGPU) has gained much attention from scientific computing in multiple domains, thus becoming an important programming model in HPC. Compute Unified Device Architecture (CUDA) has been established as a popular programming model for GPGPUs, removing the need for using the graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Moreover, jCuda is based on CUDA whereas Aparapi relies on OpenCL, but this fact is not especially relevant. A previous work [14] on the evaluation of CUDA and OpenCL, on the experimental testbed used for the performance evaluation presented in this section, has shown that CUDA and OpenCL are able to provide roughly the same performance, therefore the actual implementation of a given code is the main reason of performance differences among CUDA and OpenCL.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Moreover, jCuda is based on CUDA whereas Aparapi relies on OpenCL, but this fact is not especially relevant. A previous work [14] on the evaluation of CUDA and OpenCL, on the experimental testbed used for the performance evaluation presented in this section, has shown that CUDA and OpenCL are able to provide roughly the same performance, therefore the actual implementation of a given code is the main reason of performance differences among CUDA and OpenCL.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…• GPU Optimized VMs: The GPU-Optimized VMs are applied for compute-intensive tasks (i.e., tasks that involve huge mathematical operations). Many large-scale simulations, such as computational chemistry, rendering, and financial analysis are conducted on GPU-Optimized VMs [34]. • Storage Optimized and Dense Storage VMs: These VM types are utilized in cases where low storage cost and high data density is necessary.…”
Section: Heterogeneous Vms In Cloudmentioning
confidence: 99%
“…Running general-purpose computation on graphic processing units as a mechanism to expand current vessel capabilities is the aim of the work by Expósito et al [21]. This is a revolutionary approach within the classic vertical scalability approach in conventional data centers.…”
Section: Building the Next Generation Millennium Falconmentioning
confidence: 99%